2011
DOI: 10.1128/jcm.05053-11
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between Clinical Outcome of Clostridium difficile Infections, Strain Type, and Virulence-Associated Phenotypes

Abstract: Clostridium difficile strain NAP1/027 (North American pulsed-field gel electrophoresis [PFGE] type 1 and PCR ribotype 027 [R027]) has been associated with recent outbreaks in North America and Europe. It has been associated with more severe disease symptoms, higher mortality rates, and greater risk of relapse. This strain is thought to produce more toxins and sporulate to higher levels. However, recent studies suggest that this may not always be the case. The objective of our study was to assess, in a nonoutbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 44 publications
1
82
0
1
Order By: Relevance
“…The common occurrence of toxinotype V in the present study underscores a potential concern, as this type has been associated with community-associated disease and increasing prevalence in CDI in humans (6,21,26,27). Further investigation is necessary, as some recent reports have found toxinotype V in asymptomatic people (21), and others found that there was no association between virulence attributes and clinical outcomes (28).…”
Section: Discussionmentioning
confidence: 83%
“…The common occurrence of toxinotype V in the present study underscores a potential concern, as this type has been associated with community-associated disease and increasing prevalence in CDI in humans (6,21,26,27). Further investigation is necessary, as some recent reports have found toxinotype V in asymptomatic people (21), and others found that there was no association between virulence attributes and clinical outcomes (28).…”
Section: Discussionmentioning
confidence: 83%
“…These strains are associated with both community-acquired and health care-associated CDI. However, a preliminary review of patients with or without the 027/NAP1/BI strain did not show any significant differences in disease severity (21). Thus, this issue requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports suggested a poor correlation between the presence of tcdC or binary genes with clinical outcomes in nonepidemic settings (34,35). These studies were based on comparisons of NAP1 strains in different severity groups without a genetic comparison, or the genetic comparison was limited to tcdC and binary toxin genes.…”
Section: Discussionmentioning
confidence: 99%